The innovative research of Ukrainian scientists in the field of analysis, optimization and automation of energy systems modes in the second half of the 20th century - Tverytnykova, Elena (Estonian Association for the History and Philosophy of Science, 2017)
The article is based on a study on analysis development, optimization and automation of complex power systems modes in Ukraine in the second half of the twentieth century. The study demonstrates for the first time the deployment of innovative scientific researches according to the development of methods and software simulation for power systems, relying on archival materials contributed by Ukrainian scientists. The article also introduces the scientific school of the Institute of Electrodynamics at NAS, Ukraine involved in the field of automation of power systems modes. The scientific school, founded by academician S. A. Lebedev, has developed in the works of L. V. Tsukernik, I. M. Sirota, B. S. Stogniy, A. V. Kirilenko, V. N. Avramenko, and others. The main research areas at the Institute of Electrodynamics are calculation of transient state and the stability of power systems; calculation and analysis of normal and emergency modes; calculation of settings of protection devices; analysis and forecasting of electrical loads; and development of operational mode control issues. Also, the activities of the higher electrotechnical school are taken into consideration. In Kyiv Polytechnic Institute, under the supervision of Professor V. G. Kholmsky, the most important research on the development of calculation theory, methodology of analysis and optimization of electrical networks modes were made. Professor G. I. Denisenko at the Lviv Polytechnic Institute initiated the ground-breaking development of the simultaneous electric power transmission of AC and DC.
Keywords: Academy of Sciences of Ukraine; electrotechnics; higher technical school; Institute of electrodynamics; scientific achievement